Replacement of existing analog with digital fieldbus: A case study of raw cane sugar production - Thepmanee, Teerawat; Julsereewong, Amphawan; Julsereewong, Prasit; Jetanacheawchankij, Chaiwat (My University, 2013)
This article focuses on a digital fieldbus replacement for existing analog communications to bring automation infrastructure for operational excellence. Economic analysis between conventional and Foundation Fieldbus systems for new instrumentation and control installations in a raw cane sugar production is described as an illustrative case study. Surpassing the traditional analog system during project implementation, the digital fieldbus provides saving in material, installation, and commissioning costs. The studied case can be applied as a useful tool that can support planning and decision making for any small or large upcoming projects. © 2013 ICIC International.
Keywords: Analog; Cane sugar production; Cost saving; Digital; Fieldbus; Foundation Fieldbus; Installation